3(x+1)-1\end{array}\right\; \; \left\{\begin{array}{l}2x+6-x+8<4\\6x>3x+3-1\end{array}\right\; \; \left\{\begin{array}{l}x<-10\\3x>2\end{array}\right\\\\\\\left\{\begin{array}{l}x<-10\\x>\frac{2}{3}\end{array}\right\qquad \Rightarrow \quad x\in \varnothing" alt="\left\{\begin{array}{l}2(x+3)-(x-8)<4\\6x>3(x+1)-1\end{array}\right\; \; \left\{\begin{array}{l}2x+6-x+8<4\\6x>3x+3-1\end{array}\right\; \; \left\{\begin{array}{l}x<-10\\3x>2\end{array}\right\\\\\\\left\{\begin{array}{l}x<-10\\x>\frac{2}{3}\end{array}\right\qquad \Rightarrow \quad x\in \varnothing" align="absmiddle" class="latex-formula">